Protein Ligases: Nature’s Gift for Protein/Peptide Synthesis - Yvonne Ritsema; Huapeng Li; Qingfei Zheng (BioChem, 2025)
Proteins are structurally and functionally diverse biomacromolecules that serve a variety of essential activities to ensure complex biological homeostasis. The desire to elucidate and enhance these biological functions has been at the forefront of research for many decades. However, generating active proteins via recombinant expression or through chemical total synthesis each has limitations in terms of yield and functionality. Nature has provided a solution to this problem through evolving protein ligases that catalyze the formation of amide bonds between peptides/proteins, which can be exploited by protein engineers to develop robust functional proteins. Here, we summarize the biochemical mechanisms and applications of multiple cysteine-based protein ligases, especially focusing on how they have been utilized for protein therapeutics and engineering, as well as how they inspired chemists to develop efficient methodologies for protein synthesis (e.g., native chemical ligation).